Learning Outcomes: Safety Education for Comprehensive School Pupils - Brita Somerkoski; Tomi Kärki; Eila Lindfors (Future Academy, 2022)
This paper investigates the learning outcomes of comprehensive school pupils in the context of safety based on a quantitative research design. We considered learning and safety competence here as a combination of
knowledge, skills and attitudes. We collected the data using two questionnaires, TUKO I (n=375) and TUKO II
(n=272). Teachers and the third sector (NGO´s, non-governmental organizations) external experts carried out
safety lessons and drills in four comprehensive schools in between two data collection periods. The results of
this study show that about one third of the pupils had the good to excellent level of safety knowledge. A novel
finding of this study is that during the intervention, the primary school pupils developed their safety attitude
whereas the secondary school pupils improved their safety skills. Based on this pilot study, we can conclude that experiential learning and safety drills in schools might have an effect especially on safety attitudes and skills. However, there is a need for more research to understand the relations of cause and effect.